The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.compstruct.2016.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Trigonometric-series solution for analysis of laminated composite beams

Abstract: Northumbria University has developed Northumbria Research Link (NRL) to enable users to access the University's research output. Copyright © and moral rights for items on NRL are retained by the individual author(s) and/or other copyright owners. Single copies of full items can be reproduced, displayed or performed, and given to third parties in any format or medium for personal research or study, educational, or not-for-profit purposes without prior permission or charge, provided the authors, title and full b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
26
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 38 publications
(54 reference statements)
5
26
0
8
Order By: Relevance
“…Moreover, it is known that Ritz method is efficient to deal with composite and FG beams with arbitrary boundary conditions. The accuracy and efficiency of this approach can be found in some representative earlier works [24,26,[40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is known that Ritz method is efficient to deal with composite and FG beams with arbitrary boundary conditions. The accuracy and efficiency of this approach can be found in some representative earlier works [24,26,[40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…To understand the mechanical behavior of these structures, researchers have been developed various beam theories in recent years, the review of these theories can be found in [1]. There are a number of beam theories which have presented the kinematics of deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the attractive properties in strength, stiffness and lightness, various beam theories have been developed to understand the mechanical behavior of these structures during the last decade. In [1], the review of these theories can be found.…”
Section: Introductionmentioning
confidence: 99%
“…In [1], the trigonometric series solutions are presented for the static, buckling and free vibration responses of laminated composite beams. The vibration analysis of cross-ply laminated beams subjected to different sets of boundary conditions based on a three-degree-of-freedom shear deformable beam theory via Ritz method is presented in [37].…”
Section: Introductionmentioning
confidence: 99%